The Value of Character Education in the Novel Santri Pilihan Bunda by Salsyabila Falensia and Its Relation to Novel Text Learning in High School - Aniska Hildayatuzzahra; M. Ardi Kurniawan (Jurnal Bebasan, 2025)
This research is motivated by the lack of instillation of character education values in Indonesia, which encourages the need for optimization through various media, including literary works. The novel Santri Pilihan Bunda by Salsyabila Falensia was chosen because it contains many character values that are relevant to real life. The purpose of this research is to describe the values of character education in the novel and assess its suitability as a teaching material in learning novel texts in high school. This study uses a descriptive qualitative approach with data collection techniques in the form of reading, listening, and taking notes, as well as data analysis through reduction, presentation, and drawing conclusions. The results of the study show that this novel contains seven main characters based on Thomas Lickona's theory as many as 74 data findings, with the dominant character in the form of affection in accordance with the romance genre of the novel. In addition, this novel meets the criteria for teaching materials according to Rahmanto, namely aspects of language, psychology, and cultural background, so it is suitable as an alternative teaching material in literary learning in high school. These findings reinforce the importance of habituating character education from an early age through literary texts to shape students' morals, morals, and obedience to applicable norms.